Bioaccumulation of persistent organic pollutants in female common dolphins (Delphinus delphis) and harbour porpoises (Phocoena phocoena) from western European seas: Geographical trends, causal factors and effects on reproduction and mortality - Pierce, G; Santos, M; Murphy, S; Learmonth, J; Zuur, A; Rogan, E; Bustamante, Paco; Caurant, Florence; Lahaye, V; Ridoux, Vincent; Zegers, B; Mets, A; et al. (Environmental Pollution, 2008)
Concentrations of polychlorinated biphenyls (PCBs) in blubber of female common dolphins and harbour porpoises from the Atlantic coast of Europe were frequently above the threshold at which effects on reproduction could be expected, in 40% and 47% of cases respectively. This rose to 74% for porpoises from the Southern North Sea. PCB concentrations were also high in southern North Sea fish. The average pregnancy rate recorded in porpoises (42%) in the study area was lower than in the western Atlantic but that in common dolphins (25%) was similar to that of the western Atlantic population. Porpoises that died from disease or parasitic infection had higher concentrations of persistent organic pollutants (POPs) than animals dying from other causes. Few of the common dolphins sampled had died from disease or parasitic infection. POP profiles in common dolphin blubber were related to individual feeding history while those in porpoises were more strongly related to condition. (C) 2007 Elsevier Ltd. All rights reserved.